Comparison of Graft Uptake by Underlay and Overlay Technique in Myringoplasty - Arsalan Akhtar, Aamir Ikram, Haitham Akaash, Salman Ali, Mehreen Babar, Mahwash Umair (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to compare the effectiveness of graft uptake by underlay and overlay technique in patients undergoing myringoplasty Design of the Study: It was a randomized controlled trial Study Settings: Research was conducted at Department of Otorhinolaryngology and Head and Neck surgery Holy Family Hospital, Rawalpindi from January 2021 to June 2021. Material and Methods: In this study, 80 patients underwent myringoplasty for tympanic perforation who were randomly divided into two groups. Patients ranged in age from 20 to 40 years old. Those in Group A had an underlay myringoplasty, while those in Group B had an overlay procedure. One of the study’s outcome variables was the procedure’s effectiveness, which was observed and compared among groups. Results of the Study: There were 1.2:1 men to women patients, with 44 (55.0%) men and 36 (45.0%) women. Patients who underwent underlay versus overlay myringoplasty had a considerably greater rate of hearing improvement (97.5 percent vs. 77.5 percent ; p=0.007) and a significantly lower rate of complications (5.0 percent vs. 32.5 percent ; p=0.002). Conclusion: Underlay myringoplasty was found to be much more successful than overlay myringoplasty in 95.0 percent of patients compared to 57.5 percent of patients who received overlay myringoplasty.